Genome-wide association study of the fatty liver index in the Taiwanese population reveals shared and population-specific genetic risk factors across ethnicities - Pei Pei Lau; Chun-Yu Wei; Min-Rou Lin; Wan-Hsuan Chou; Yu-Jui Yvonne Wan; Wei-Chiao Chang (Cell & Bioscience)
Abstract Background and objectives Although the incidence of fatty liver disease (FLD) is increasing worldwide, the genetic basis of this disease is not fully understood. This study uses the fatty liver index (FLI) to identify and compare genetic variants associated with FLD in Taiwanese and European populations. Results In this study, a total of 145,356 Taiwan Biobank participants were included in the discovery analysis. Subjects with elevated FLI were found to have a significantly greater risk of developing FLD, as confirmed by imaging data (OR: 4.43; 95% CI: 3.88–5.06). Through genome-wide association studies (GWAS), we identified 6 variants previously associated with nonalcoholic fatty liver disease (NAFLD) and validated 50 shared risk variants located in ZPR1 and FTO between the Taiwanese and European populations. Conditional analysis of 423 significant variants from FLI-defined FLD further revealed 16 independent variants within 14 genes. Pathway analysis of GWAS significant genes revealed that lipid metabolism and the peroxisome proliferator-activated receptor (PPAR) signaling pathway are causes of hepatic fat accumulation. Conclusion This study identified six independent NAFLD-associated variants in GCKR, LPL, TRIB1AL, and FTO and emphasized ZPR1 and FTO as shared risk genes for FLI-defined FLD in both Taiwanese and European populations. These findings support the utility of the FLI for FLD prediction, provide new genetic insights, and reveal the common genetic pathways of FLD across two ethnic groups. This research offers a valuable framework for advancing personalized medicine and therapeutic strategies for FLD.